2013
DOI: 10.1097/acm.0b013e31828577fe
|View full text |Cite
|
Sign up to set email alerts
|

Do Canadian Researchers and the Lay Public Prioritize Biomedical Research Outcomes Equally? A Choice Experiment

Abstract: Citizens and researchers fundamentally prioritized the same outcomes for basic biomedical research. Notably, they prioritized traditional scientific outcomes and disvalued the pursuit of economic returns. These findings have implications for how academic medicine assigns incentives and value to basic health research and how biomedical researchers and the public may jointly contribute to setting the future research agenda.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
1
14
2
Order By: Relevance
“…However, there remains a lack of methodological and empirical research on how the public value research impact 14 15 and how valuations may vary between stakeholder groups. 16 To address this issue, we undertook online surveys with a representative sample of the UK public as well as current and recent Medical Research Council (MRC) grant holders to elicit their relative valuation of different types of research impact. Using a method known as 'best-worst scaling' (BWS), 17 we asked survey participants to compare statements about different types of impact.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there remains a lack of methodological and empirical research on how the public value research impact 14 15 and how valuations may vary between stakeholder groups. 16 To address this issue, we undertook online surveys with a representative sample of the UK public as well as current and recent Medical Research Council (MRC) grant holders to elicit their relative valuation of different types of research impact. Using a method known as 'best-worst scaling' (BWS), 17 we asked survey participants to compare statements about different types of impact.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The survey assessed preferences for research outcomes across five attributes using a discrete choice experiment. 16 The authors concluded that citizens and researchers fundamentally prioritised the same outcomes for basic biomedical research. Notably, they prioritised traditional scientific outcomes and devalued the pursuit of economic returns.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Further, our completion rate is typical of internet surveys that target samples representing the population on key demographic criteria. 26,41,42,43 Although individuals who earn less and have less formal education were under-represented, bivariate analyses demonstrated that the attitudes and beliefs examined did not differ significantly along these characteristics (data not shown). Further, our findings on the predictors of reduced obligations to participate in WG/ES-based NBS were based on a smaller sub-sample of 472 and should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 95%
“…These studies suggest differing levels of alignment between researcher and public views, emphasizing the importance of the question for research impact evaluation. In both studies, however, both researchers and the public showed a preference for health-related over economic or commercial outcomes (Miller et al, 2013;Pollitt et al, 2016).…”
Section: Socially-desirable Impact Goalsmentioning
confidence: 99%
“…There is limited empirical evidence on the variation in views about impact from research. Two studies, focusing on medical research, have examined the preferences of researchers and the public with respects to research impact (Miller et al, 2013;Pollitt et al, 2016). These studies suggest differing levels of alignment between researcher and public views, emphasizing the importance of the question for research impact evaluation.…”
Section: Socially-desirable Impact Goalsmentioning
confidence: 99%